O Pensar Alto em Grupo aliado com Anne with an E: visando à formação de leitores literários na adolescência - Faria, Juliana Carolina (2023)
This interpretative qualitative paradigm research (BORTONI-RICARDO, 2008; MOITA LOPES, 1994), which is within the area of Applied Linguistics, aims to: 1. interweave the message conveyed by the Anne with an E series and the voices of teenagers in order to investigate whether the relationships between the series and the reading they do are effective for carrying out deep reading; and 2. investigate whether the dialogical reading carried out between/with the students through poems and scenes from the series contributes to stimulating the formation of literary readers in adolescence. These objectives were coined from the initial questions: 1. how the mediation of digital technology in the school space can (or cannot) favor deep reading?; and 2. to what extent can the Group Think-Aloud (ZANOTTO, 1995, 2014, 2016) as a dialogical literacy practice instigate changes in students' views on reading and themselves as readers?. The Group Think-Aloud (PAG) makes it possible to give voice to readers and, consequently, to work on reading in a collaborative and profound way, this work being the first to apply it with a television resource. The research has the participation of students inserted in a context of the end of Elementary School II - ninth year - of a private school in the interior of São Paulo. Regarding the Canadian series Anne with an E (Netflix 2017-2020), it was used as a way to involve students in a context of reflection about the reading habit represented in the episodes and in the poems it presents, also stimulating the practice of reading in a media resource. After all, although the television series has entertainment as its initial objective, it goes beyond the field of fiction and addresses themes that are extremely relevant to the formation of the child-adolescent. In this way, a theoretical-methodological perspective is used that underlies mediatization within the classroom, the concept of multiliteracies and multimodality (KALANTZIS; COPE; PINHEIRO, 2020) and Educommunication (SOARES, 2011, 2015; MARTÍN-BARBERO, 2014) in order to bring forth the students' autonomy and freedom in contact with literature. So that data could be generated, the first step was to conduct a semi-structured group interview to understand their tastes in relation to books and series and what relationship they had with reading; then, the Group Think-Aloud to enable the sharing of ideas and the shared construction of multiple readings; and, finally, an individual questionnaire via Google Forms. The data revealed that this dialogical literacy practice, as argued by Zanotto (2016), allows students to become responsive and critical readers, in addition to enabling them to build a sensitized look and a welcoming posture towards the other, whether this other person is the one directly next to them or the other one presented in texts